Giant cell tumor of the thumb proximal phalanx: resection-iliac graft and double arthrodesis - Fnini, S; Labsaili, N; Messoudi, A; Largab, A (Chirurgie de la main, 2008)
Giant cell tumours (GCT) of bone are frequent, with variable behaviour, high risk of recurrence and an often benign histological appearance. Their location in the hand is uncommon, and there are few publications on the subject. Surgical treatment as described in the literature is very variable. We report a case of recurrent grade II GCT, arising in the proximal phalanx of the thumb, aggressive and causing a pathological fracture. After a surgical biopsy, we performed an "en bloc" resection of the first phalanx, with an iliac crest graft reconstruction and a double arthrodesis of the metacarpophalangeal and interphalangeal joint. No recurrence or lung metastasis was seen at 18 months follow-up.